Sensing material for high-performance detection of luteolin, preparation method of sensing material and sensor
By adopting ternary system sensing materials of SnO2, carbon nanotubes and ZIF-67, the problem of complex preparation and low sensitivity of luteolin detection samples in the prior art is solved, and high performance detection is achieved, with low detection limit and high sensitivity.
Patent Information
- Application Number
- CN202510011161.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-11
AI Technical Summary
The prior art samples are complex in the detection of luteolin, with low sensitivity, making it difficult to achieve efficient and accurate detection.
The ternary system sensing material of SnO2, carbon nanotubes and ZIF-67 is used to prepare the sensing material through ultrasonic treatment, centrifugation, washing and vacuum drying, and is modified on the electrode surface to form the SnO2-CNT-ZIF-67/GCE modified electrode.
It realizes high-performance detection of luteolin, has low detection limit and high sensitivity, and has a wide detection range, which is suitable for the concentration range of 0.01-3000nM.
Smart Images

Figure CN119797417A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrochemical detection, and particularly relates to a sensing material for high-performance detection of luteolin and a preparation method and a sensor thereof. Background Art
[0002] Luteolin has significant medical benefits and can reduce the risk of chronic diseases such as cancer, cardiovascular disease and neurodegenerative diseases. Given the widely recognized medicinal value of luteolin, it is necessary to analyze its content to accurately determine its concentration and ensure the uniformity and effectiveness of pharmaceutical preparations, herbal supplements and functional foods that claim to contain this beneficial compound. Traditional luteolin detection methods include chromatography and spectral analysis, but they have complex sample preparation, low sensitivity and poor detection effect.
[0003] Therefore, there is an urgent need for a sensor material or method that can detect luteolin conveniently and quickly, with a low detection limit and high sensitivity to make up for the shortcomings of existing methods. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a sensing material and a preparation method and a sensor for high-performance detection of luteolin. The sensing material prepared by the present invention can specifically detect luteolin without the need to prepare complex samples, and has the effects of low detection limit and high sensitivity.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] In a first aspect, the present invention provides a method for preparing a sensing material for high-performance detection of luteolin, comprising the following steps:
[0007] S1. SnCl4·5H2O, ethanol solution and NaOH are mixed and ultrasonically treated, and then carbon nanotubes are added and ultrasonically treated to obtain a mixed solution;
[0008] S2. The mixed solution is reacted in a high pressure reactor to obtain a reaction material;
[0009] S3. The reaction material is sequentially centrifuged, washed, and vacuum dried to obtain a SnO2-CNT composite material;
[0010] S4. The SnO2-CNT composite material, ZIF-67 and ethanol are mixed and then ultrasonically treated, stirred, centrifuged, washed and dried in sequence to obtain the SnO2-CNT-ZIF-67 sensing material.
[0011] Preferably, the mass volume ratio of SnCl4·5H2O, ethanol solution, NaOH and carbon nanotubes in S1 is: 0.75-0.95 g: 40-60 mL: 8-12 mg: 0.35-0.45 g.
[0012] More preferably, the volume concentration of the ethanol solution is 50%.
[0013] Preferably, the ultrasonic time in S1 is 5 to 10 minutes.
[0014] Preferably, the reaction temperature in S2 is 180-190° C., and the reaction time is 12-18 h.
[0015] Preferably, each step in S3 satisfies one or more of the following conditions:
[0016] The centrifugal separation speed is 5000-12000rpm;
[0017] Wash with ethanol and water alternately 3-5 times;
[0018] The vacuum drying temperature is 40-60°C and the time is 10-16h.
[0019] Preferably, the mass volume ratio of SnO2-CNT composite material, ZIF-67 and ethanol in S4 is 0.1-0.2g: 0.15-0.3g: 25-35mL.
[0020] Preferably, each step in S4 satisfies one or more of the following conditions:
[0021] Ultrasonication time is 5 to 10 minutes;
[0022] The stirring temperature is 23-25°C and the stirring time is 12h;
[0023] The centrifugal separation speed is 6000-12000rpm;
[0024] Wash with ethanol 3-4 times;
[0025] The vacuum drying temperature is 40-60°C and the time is 10-16h.
[0026] In a second aspect, the present invention provides a sensing material for high-performance detection of luteolin, which is prepared by the preparation method described above.
[0027] In a third aspect, the present invention provides a sensor for high-performance detection of luteolin, comprising the following preparation steps:
[0028] Polish the GCE electrode;
[0029] The SnO2-CNT-ZIF-67 sensor material, ethanol, ultrapure water and 0.5% naphthol are mixed and then ultrasonically dispersed to obtain a dispersion;
[0030] The dispersion was dripped onto the polished surface of the GCE electrode and naturally air-dried to obtain the SnO2-CNT-ZIF-67 / GCE modified electrode.
[0031] Preferably, the GCE electrode is polished with 0.3 μm and 0.05 μm Al2O3 powder to remove the oxide layer on the electrode surface. After polishing, the polished GCE is tested by cyclic voltammetry in a solution of 5 mM K3[Fe(CN)6], 5 mM K4[Fe(CN)6] and 0.1 M KCl, where the scan rate is 100 mV and the potential region is -0.2-0.6 V. When the potential difference between the oxidation peak and the reduction peak is less than 100 mV, the electrode polishing is considered to be completed.
[0032] Preferably, the mass volume ratio of the SnO2-CNT-ZIF-67 sensing material, ethanol, ultrapure water, and 0.5% naphthol is 1 mg: 400 uL: 600 uL: 10 uL.
[0033] Preferably, the amount of the dispersion is 5uL / cm 2 .
[0034] Beneficial technical effects:
[0035] The present invention uses the ternary system sensing material of SnO2, carbon nanotubes and ZIF-67 for the detection of luteolin for the first time; moreover, the preparation process of the sensing material is simple, the raw materials are easily available, and the prepared sensing electrode has good sensing performance, a wide linear range, a low detection limit and a high sensitivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 The XRD patterns of the sensing materials obtained in Example 1 and Comparative Examples 1 to 2 are as follows;
[0037] Figure 2 The SEM images of the sensing materials obtained in Example 1 and Comparative Examples 1-2 are shown;
[0038] Figure 3 The BET spectra of the sensing materials obtained in Example 1 and Comparative Examples 1-2;
[0039] Figure 4 The CV curve of the sensor prepared by the sensing material of Example 1 detecting luteolin;
[0040] Figure 5 This is a performance test diagram of the sensor prepared with the sensing material of Example 1 for detecting luteolin. DETAILED DESCRIPTION
[0041] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.
[0042] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0043] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0044] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0045] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0046] The "room temperature" and "normal temperature" mentioned in the present invention are all calculated as 25±2°C unless otherwise specified.
[0047] The raw materials and instruments used in the following examples of the present invention are commercially available unless otherwise specified.
[0048] Example 1
[0049] This embodiment provides a sensing material for high-performance detection of luteolin, and the preparation method is as follows:
[0050] S1. Weigh 0.75 g SnCl4·5H2O into a beaker containing 40 mL of a mixture of ethanol and water (1:1, v / v), then add 8 mg NaOH, sonicate for 5 min, then add 0.35 g carbon nanotubes (CNT) and sonicate for 10 min to obtain a uniform mixture;
[0051] S2. The mixture was transferred to a high pressure reactor and heated at 185 ° C for 16 h. After the reaction was completed, it was naturally cooled to room temperature to obtain a reaction material;
[0052] S3. The reaction material was centrifuged at 5000 rpm, washed alternately with ethanol and water 5 times, and dried under vacuum at 60 ° C for 12 h to obtain a black SnO2-CNT composite material;
[0053] S4. Take 0.1g of SnO2-CNT composite material and 0.15g of ZIF-67, add them into 25ml of ethanol, ultrasonicate for 10 minutes, stir at room temperature for 12h, centrifuge at 6000rpm after the reaction, collect the black purple precipitate, wash it 3 times with ethanol, and vacuum dry it at 60℃ for 12h to obtain SnO2-CNT-ZIF-67 sensing material.
[0054] Example 2
[0055] This embodiment provides a sensing material for high-performance detection of luteolin, and the preparation method is as follows:
[0056] S1. Weigh 0.85 g SnCl4·5H2O into a beaker containing 50 mL of a mixture of ethanol and water (1:1, v / v), then add 10 mg NaOH, sonicate for 8 min, then add 0.4 g carbon nanotubes (CNT) and sonicate for 10 min to obtain a uniform mixture;
[0057] S2. The mixture was transferred to a high pressure reactor and heated at 180 ° C for 12 h. After the reaction was completed, it was naturally cooled to room temperature to obtain a reaction material;
[0058] S3. The reaction material was centrifuged at 8000 rpm, washed alternately with ethanol and water three times, and dried under vacuum at 40 ° C for 10 h to obtain a black SnO2-CNT composite material;
[0059] S4. Take 0.2g of SnO2-CNT composite material and 0.3g of ZIF-67, add them into 35ml of ethanol, ultrasonicate for 10 minutes, stir at room temperature for 12h, centrifuge at 8000rpm after the reaction, collect the black purple precipitate, wash it with ethanol for 3 times, and vacuum dry it at 40℃ for 16h to obtain SnO2-CNT-ZIF-67 sensing material.
[0060] Example 3
[0061] This embodiment provides a sensing material for high-performance detection of luteolin, and the preparation method is as follows:
[0062] S1. Weigh 0.95 g SnCl4·5H2O into a beaker containing 60 mL of a mixture of ethanol and water (1:1, v / v), then add 12 mg NaOH, sonicate for 7 min, then add 0.45 g carbon nanotubes (CNTs) and sonicate for 10 min to obtain a uniform mixture;
[0063] S2. The mixture was transferred to a high pressure reactor and heated at 190 ° C for 18 h. After the reaction was completed, it was naturally cooled to room temperature to obtain a reaction material;
[0064] S3. The reaction material was centrifuged at 10000 rpm, washed alternately with ethanol and water 5 times, and dried under vacuum at 60 ° C for 16 h to obtain a black SnO2-CNT composite material;
[0065] S4. Take 0.1g of SnO2-CNT composite material and 0.3g of ZIF-67, add them into 25ml of ethanol, ultrasonicate for 10 minutes, stir at room temperature for 12h, centrifuge at 12000rpm after the reaction, collect the black purple precipitate, wash it 3 times with ethanol, and vacuum dry it at 60℃ for 10h to obtain SnO2-CNT-ZIF-67 sensing material.
[0066] Comparative Example 1
[0067] This comparative example provides a SnO2 composite sensing material, and the preparation method is as follows:
[0068] 0.75 g SnCl4·5H2O was weighed and added into a beaker containing 40 mL of a mixture of ethanol and water (1:1, v / v), and then 8 mg NaOH was added and ultrasonicated for 5 min to obtain a uniform mixture.
[0069] The above solution was transferred to a high-pressure reactor and heated at 185°C for 16 hours. After the reaction was completed, it was naturally cooled to room temperature to obtain a white product. The white product was centrifuged at 5000 rpm, washed alternately with ethanol and water for at least 3 times, and vacuum dried at 60°C for 12 hours to obtain a white SnO2 composite material.
[0070] Comparative Example 2
[0071] This comparative example provides a SnO2-CNT composite sensing material, and the preparation method is as follows:
[0072] 0.75 g SnCl4·5H2O was weighed and added into a beaker containing 40 mL of a mixture of ethanol and water (1:1, v / v), and then 8 mg NaOH was added and ultrasonicated for 5 min. Then, 0.35 g carbon nanotubes (CNTs) were added and ultrasonicated for 10 min to obtain a uniform mixed solution.
[0073] The dispersion was transferred to a high-pressure reactor and heated at 185°C for 16 hours. After the reaction was completed, it was naturally cooled to room temperature to obtain a black product. The black product was centrifuged at 5000 rpm, and washed alternately with ethanol and water at least 40°C-60°C for 10-16 hours, and vacuum dried at 60°C for 12 hours to obtain a black SnO2-CNT composite material.
[0074] Experimental Example 1
[0075] XRD spectrum analysis:
[0076] like Figure 1 As shown in the figure, the synthesized SnO2 has (110), (101), (200), (211), (220) crystal plane peaks at 26.8°, 34.1°, 37.9°, 52.1°, and 54.8°, which is consistent with the crystal structure of tetragonal SnO2 (corresponding card JCPDS#41-1445). In the SnO2-CNT material, we did not observe additional CNT peaks because CNT is an amorphous structure. For the SnO2-CNT-ZIF-67 material, some additional typical ZIF-67 crystal peaks appeared, which also indicates the presence of ZIF-67 in the composite material. Note that whether it is SnO2-CNT-ZIF-67 or SnO2-CNT material, the (110) crystal plane of SnO2 crystal is shifted to the left to a diffraction angle of 26.4°, which indicates that there is a significant interaction between SnO2 and CNT.
[0077] Experimental Example 2
[0078] Structural characterization:
[0079] like Figure 2 As shown in the figure, the SnO2 material is an aggregate composed of nanoparticles (a); after being compounded with CNT, SnO2 can be well modified on CNT to form a 3D spatial structure (b), which indicates that there should be a strong interaction between the two. After SnO2-CNT reacts with ZIF-67, a SnO2-CNT-ZIF-67 three-dimensional composite material is obtained (c), in which ZIF-67 still maintains a good regular dodecahedron structure, and some SnO2 particles are modified on its surface.
[0080] Experimental Example 3
[0081] BET spectrum analysis:
[0082] Figure 3 The N2 adsorption-desorption curve test curve of the prepared materials. The calculated specific surface areas of SnO2, SnO2-CNT and SnO2-CNT-ZIF-67 materials are 109m 2 / g, 124m 2 / g and 374m 2 / g. This indicates that the composite material has a larger specific surface area and may provide more active sites for the detection of luteolin.
[0083] Experimental Example 4
[0084] Sensing material detection of luteolin performance test
[0085] 1. Preparation of sensing materials for high-performance detection of luteolin
[0086] Electrode polishing:
[0087] The GCE electrode was polished with 0.3 μm and 0.05 μm Al2O3 powders to remove the oxide layer on the electrode surface, and the polished GCE was tested by cyclic voltammetry in a solution of 5 mM K3[Fe(CN)6], 5 mM K4[Fe(CN)6] and 0.1 M KCl, with a scan rate of 100 mV and a potential region of -0.2-0.6 V. The electrode polishing was completed when the potential difference between the oxidation peak and the reduction peak was less than 100 mV.
[0088] Sensing material and polished electrode composite:
[0089] Take 1 mg of the sensing material obtained in Example 1, then add 400 uL of ethanol, 600 uL of ultrapure water, and 10 uL of 0.5% naphthol for ultrasonic dispersion to obtain a uniform dispersion, take 5 uL of the above dispersion and titrate it onto the polished electrode surface, and naturally air-dry to obtain an electrode for high-performance detection of luteolin.
[0090] 2. Linear relationship detection
[0091] like Figure 4 As shown in a, when the luteolin high-performance detection electrode prepared by the present invention detects 100nM luteolin (dissolved in BR buffer, pH: 4.5), the cyclic voltammetry (CV) curve shows regular changes in the redox signal as the scan rate increases, the redox peak intensity gradually increases, the oxidation peak potential moves to the right, and the reduction peak potential moves to the left. The peak voltage and the logarithm of the scan rate show a linear relationship ( Figure 4 b), the charge transfer coefficient is calculated to be 0.54 and the charge transfer number is 0.87, indicating that the reaction is a single-electron reaction process.
[0092] 3. Sensitivity and detection limit detection
[0093] like Figure 5 As shown in a, the differential pulse voltammetry (DPV) response diagram of the luteolin high-performance detection electrode prepared by the present invention to different concentrations of luteolin (dissolved in BR buffer, pH: 4.5). The relationship between the corresponding DPV peak current and concentration is shown in Figure 5 As shown in b, the DPV peak current showed a linear correlation with luteolin in the concentration ranges of 0.01-50nM and 50-3000nM, respectively. The overall linear range was: 0.01-3000nM, the highest sensitivity of detection was 70.4uA / uM, and the detection limit was 0.14nM.
[0094] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a sensing material for high-performance detection of luteolin, characterized in that: The following steps are involved: S1. SnCl4·5H2O, ethanol solution and NaOH are mixed and ultrasonically treated, and then carbon nanotubes are added and ultrasonically treated to obtain a mixed solution; S2. The mixed solution is reacted in a high pressure reactor to obtain a reaction material; S3. The reaction material is sequentially centrifuged, washed, and vacuum dried to obtain a SnO2-CNT composite material; S4. The SnO2-CNT composite material, ZIF-67 and ethanol are mixed and then ultrasonically treated, stirred, centrifuged, washed and dried in sequence to obtain the SnO2-CNT-ZIF-67 sensing material.
2. The preparation method according to claim 1, characterized in that: The mass volume ratio of SnCl4·5H2O, ethanol solution, NaOH and carbon nanotubes in S1 is: 0.75-0.95g: 40-60mL: 8-12mg: 0.35-0.45g; The volume concentration of the ethanol solution is 50%.
3. The preparation method according to claim 1, characterized in that: The reaction temperature in S2 is 180-190° C., and the reaction time is 12-18 hours.
4. The preparation method according to claim 1, characterized in that: Each step in S3 satisfies one or more of the following conditions: The centrifugal separation speed is 5000-12000rpm; Wash with ethanol and water alternately 3-5 times; The vacuum drying temperature is 40-60°C and the time is 10-16h.
5. The preparation method according to claim 1, characterized in that: The mass volume ratio of the SnO2-CNT composite material, ZIF-67 and ethanol in the S4 is 0.1-0.2 g: 0.15-0.3 g: 25-35 mL.
6. The preparation method according to claim 1, characterized in that: Each step in S4 satisfies one or more of the following conditions: Ultrasonication time is 5 to 10 minutes; The stirring temperature is 23-25°C and the stirring time is 12h; The centrifugal separation speed is 6000-12000rpm; Wash with ethanol 3-4 times; The vacuum drying temperature is 40-60°C and the time is 10-16h.
7. A sensing material for high-performance detection of luteolin, prepared by the preparation method according to any one of claims 1 to 6.
8. A sensor for high-performance detection of luteolin, characterized in that: The method comprises the following preparation steps: Polish the GCE electrode; The SnO2-CNT-ZIF-67 sensing material according to claim 1, ethanol, ultrapure water, and 0.5% naphthol are mixed and ultrasonically dispersed to obtain a dispersion; The dispersion was dripped onto the polished surface of the GCE electrode and naturally air-dried to obtain the SnO2-CNT-ZIF-67 / GCE modified electrode.
9. The preparation method according to claim 8, characterized in that: The mass volume ratio of the SnO2-CNT-ZIF-67 sensing material, ethanol, ultrapure water, and 0.5% naphthol is 1 mg: 400 uL: 600 uL: 10 uL.
10. The preparation method according to claim 8, characterized in that: The amount of the dispersion is 5uL / cm 2 .